Campania electorală în teritoriu: aspecte empirice ale marketingului politic (Local electoral strategies: the empirical matters of the political marketing) - Silvia ROTARU (Polis: Revista de Stiinte Politice, 2015)
The study below aims to put together the main electoral strategies and instruments for the local campaigns. Basically, this is a theoretical illustration of the steps that should be made in different constituencies in the electoral process and it can be a useful guide for politicians or campaign managers.